DEVELOPMENT OF ELECTRONIC-BASED LEARNING MEDIA APPLICATIONS ON THEME 6 "HEAT AND ITS TRANSFER" FOR CLASS V IN ELEMENTARY SCHOOL - Desy Ratna Sari; Nazurty Nazurty; Syahrial Syahrial (Jurnal Mantik, 2022)
Learning media is needed in helping students understand a material. This study aims to see how the application of electronic-based learning media in terms of material validation, media validation and testing to students. The method used is development research using the ADDIE model. From the results obtained thatThe level of material validity obtained from the material validator is 4.0 with the Very Valid category and the media validity validator obtained is 5.0 with the Very Valid category. The practical stage of the application of electronic-based learning media on the theme of 6 sub-themes of heat and its transfer was obtained from the teacher's response questionnaire and student responses. The teacher's response got a score with an average of 4.8 and 4.9 respectively in the Very Practical category, student responses got a percentage of 86% in the very practical category.